Emergence of Arctic-like Rabies Lineage in India - Nadin-Davis, Susan A.; Turner, Geoff; Paul, Joel P. V.; Madhusudana, Shampur N.; Wandeler, Alexander I.
A collection of 37 rabies-infected samples, 10 human saliva and 27 animal brain, were recovered during 2001-2004 from the cities of Bangalore and Hyderabad in southern India and from Kasauli, a mountainous region in Himachal Pradesh, northern India. Phylogenetic analysis of partial N gene nucleotide sequences of these 37 specimens and 1 archival specimen identified 2 groups, divided according to their geographic (north or south) origins. Comparison of selected Indian viruses with representative rabies viruses recovered worldwide showed a close association of all Indian isolates with the circumpolar Arctic rabies lineage distributed throughout northern latitudes of North America and Europe and other viruses recovered from several Asian countries.